Method for resource utilization of electrolytic manganese residue

CN118851724BActive Publication Date: 2026-10-16SHANDONG XIEHE UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410883497.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-03
Publication Date
2026-10-16
Estimated Expiration
2044-07-03

AI Technical Summary

Technical Problem

目前,处理和回收利用电解锰渣的研究主要集中在回收提取锰、硫酸铵及其他有价金属,而提取锰或其他有价金属后的残渣则作为建筑材料使用,但是目前以该残渣为原料制备的建筑材料密度大,且对电磁波的吸收弱

Benefits of technology

[0018] This invention provides a method for the resource utilization of electrolytic manganese slag, comprising the following steps: (1) leaching the electrolytic manganese slag with acid to obtain a leachate; (2) recovering manganese, cobalt, and nickel elements from the leachate to obtain secondary waste residue; (3) mixing the secondary waste residue with waste biomass residue, and sequentially performing ball milling, cold pressing, and sintering to obtain an electromagnetic wave absorbing material. This invention first uses acid leaching to extract precious metal ions such as manganese, cobalt, and nickel from the electrolytic manganese slag. Then, the secondary waste residue obtained from acid leaching is mixed with waste biomass residue and sintered. During the sintering process, the components of the secondary waste residue itself (mainly silicon dioxide and iron oxide) hardly react and maintain the integrity of the main structure. The biomass residue, mainly composed of carbon, reacts and forms a porous structure both macroscopically and microscopically, reducing material weight while improving impedance matching. Therefore, the resource utilization method provided by this invention recovers precious metals from the electrolytic manganese slag and also prepares a lightweight and efficient electromagnetic wave absorbing material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851724B_ABST
    Figure CN118851724B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of waste recycling, in particular to a resource utilization method of electrolytic manganese residue.The present application extracts noble metal ions such as manganese, cobalt and nickel in electrolytic manganese residue by using acid leaching method, and then mixes the secondary waste residue obtained by acid leaching with waste biomass residue, and sintering, in the sintering process, the secondary waste residue itself (mainly composed of silicon dioxide and iron oxide) hardly reacts and maintains the structural integrity, and the biomass residue mainly composed of carbon forms a porous structure in macro and micro after reaction, which reduces the material quality and improves the impedance matching at the same time.Therefore, the resource utilization method provided by the present application recovers the noble metals in electrolytic manganese residue, and also prepares light and efficient electromagnetic wave absorbing building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waste recycling technology, and specifically to a method for the resource utilization of electrolytic manganese slag. Background Technology

[0002] Electrolytic manganese slag is the filter residue produced during the leaching of manganese ore powder with sulfuric acid. Due to limitations in the leaching process, pressure filtration process, and the water-holding capacity of the manganese slag itself, the dewatered manganese slag still contains about 30% water, with a manganese concentration of 35-40 g / L, still possessing considerable recycling value. Currently, research on the treatment and recycling of electrolytic manganese slag mainly focuses on the recovery and extraction of manganese, ammonium sulfate, and other valuable metals. The residue after the extraction of manganese or other valuable metals is used as a building material. However, building materials prepared from this residue currently have a high density and weak absorption of electromagnetic waves. Summary of the Invention

[0003] To address the problems existing in the prior art, this invention provides a method for the resource utilization of electrolytic manganese slag. The electromagnetic wave absorbing material obtained by the resource utilization method provided by this invention has the advantages of being lightweight and having high electromagnetic wave absorption.

[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0005] This invention provides a method for the resource utilization of electrolytic manganese slag, comprising the following steps:

[0006] (1) Using acid to leach electrolytic manganese slag to obtain leachate;

[0007] (2) After recovering manganese, cobalt and nickel elements from the leaching solution, secondary waste residue is obtained;

[0008] (3) The secondary waste residue is mixed with waste biomass residue and then ball-milled, cold-pressed and sintered in sequence to obtain electromagnetic wave absorbing material.

[0009] Preferably, the acid is sulfuric acid; the ratio of the electrolytic manganese slag to the acid is 1 kg: 3-5 L.

[0010] Preferably, the extraction temperature is 60-70°C and the extraction time is 1.5-3 hours.

[0011] Preferably, after obtaining the secondary waste residue, the process further includes washing and drying the secondary waste residue; the washing is a sequential process of water washing and alkaline washing.

[0012] Preferably, the waste biomass residue includes one or more of the following: soybean residue, sweet potato residue, kudzu root residue, areca nut residue, sugarcane residue, and corn residue.

[0013] Preferably, the mass ratio of the secondary waste residue to the waste biomass residue is 1:0.05 to 0.2.

[0014] Preferably, the cold pressing pressure is 8-12 MPa, and the holding time is 1-2 min.

[0015] Preferably, the sintering temperature is 950–1050°C, and the holding time is 1–2 hours.

[0016] Preferably, the heating rate to the sintering temperature is 3-5 °C / min.

[0017] Preferably, the leachate includes iron ions, calcium ions, magnesium ions, manganese ions, cobalt ions, and nickel ions.

[0018] This invention provides a method for the resource utilization of electrolytic manganese slag, comprising the following steps: (1) leaching the electrolytic manganese slag with acid to obtain a leachate; (2) recovering manganese, cobalt, and nickel elements from the leachate to obtain secondary waste residue; (3) mixing the secondary waste residue with waste biomass residue, and sequentially performing ball milling, cold pressing, and sintering to obtain an electromagnetic wave absorbing material. This invention first uses acid leaching to extract precious metal ions such as manganese, cobalt, and nickel from the electrolytic manganese slag. Then, the secondary waste residue obtained from acid leaching is mixed with waste biomass residue and sintered. During the sintering process, the components of the secondary waste residue itself (mainly silicon dioxide and iron oxide) hardly react and maintain the integrity of the main structure. The biomass residue, mainly composed of carbon, reacts and forms a porous structure both macroscopically and microscopically, reducing material weight while improving impedance matching. Therefore, the resource utilization method provided by this invention recovers precious metals from the electrolytic manganese slag and also prepares a lightweight and efficient electromagnetic wave absorbing material. Attached Figure Description

[0019] Figure 1 SEM image of EMRs / C-1 prepared in Example 1;

[0020] Figure 2 SEM image of EMRs / C-2 prepared in Example 2;

[0021] Figure 3 The electromagnetic wave absorption performance diagram of EMRs / C-2 prepared in Example 2 is shown.

[0022] Figure 4 The image shows the SEM image of EMRs / C-3 prepared in Example 3. Detailed Implementation

[0023] This invention provides a comprehensive recycling and treatment method for electrolytic manganese slag, comprising the following steps:

[0024] (1) Using acid to leach electrolytic manganese slag to obtain leachate;

[0025] (2) After recovering manganese, cobalt and nickel elements from the leaching solution, secondary waste residue is obtained;

[0026] (3) The secondary waste residue is mixed with waste biomass residue and then ball-milled, cold-pressed and sintered in sequence to obtain electromagnetic wave absorbing building materials.

[0027] This invention utilizes acid to leach electrolytic manganese slag to obtain an extract.

[0028] In this invention, the acid is preferably sulfuric acid; the concentration of the sulfuric acid is preferably 0.8–1.5 mol / L, more preferably 1.0 mol / L. In this invention, the ratio of electrolytic manganese slag to acid is preferably 1 kg: 3–5 L, more preferably 1 kg: 3 L.

[0029] In this invention, the extraction temperature is preferably 60-70°C, more preferably 65°C; the extraction time is preferably 1.5-3 hours, more preferably 3 hours.

[0030] After obtaining the leachate, the present invention recovers the manganese, cobalt and nickel elements in the leachate to obtain secondary waste residue.

[0031] In this invention, the step of recovering manganese, cobalt, and nickel elements from the leachate is as follows:

[0032] (1) The extract and calcium carbonate are mixed to form ferric hydroxide precipitate, and then filtered to obtain the first filtrate and the first filter residue.

[0033] (2) Add manganese fluoride to the first filtrate to form calcium fluoride and magnesium fluoride, filter, and obtain the second filtrate and the second filter residue.

[0034] (3) Mix the second filtrate with a phosphoric acid extractant, extract manganese, and then filter to obtain the third filtrate and the third filter residue;

[0035] (4) Cobalt and nickel elements are extracted again using phosphoric acid extractant P507, filtered, and cobalt-nickel catalyst and fourth filter residue are obtained; the first to fourth filter residues are combined to obtain secondary waste residue;

[0036] In this invention, the recovered precious metal ions such as manganese, cobalt, and nickel are used as precursors for battery materials or as doping modifiers for battery materials.

[0037] After obtaining the secondary waste residue, the process preferably further includes washing and drying the secondary waste residue in sequence; the washing is preferably water washing and alkali washing; the reagent for alkali washing preferably includes one or more of sodium hydroxide solution, calcium hydroxide solution and sodium carbonate solution, more preferably sodium hydroxide solution.

[0038] After obtaining the secondary waste residue, the present invention mixes the secondary waste residue with waste biomass residue, and sequentially performs ball milling, cold pressing and sintering to obtain electromagnetic wave absorbing material.

[0039] In this invention, the waste biomass residue includes one or more of the following: soybean residue, sweet potato residue, kudzu root residue, areca nut residue, sugarcane bagasse, and corn residue. In this invention, the mass ratio of the secondary waste residue to the waste biomass residue is preferably 1:0.05–0.2, more preferably 1:15.

[0040] In this invention, the grinding balls used in the ball mill are preferably made of agate balls; the ball-to-material ratio is preferably 2-5:1, more preferably 3:1. In this invention, the ball milling is preferably performed to a particle size of 0.1-0.25 mm, more preferably 0.17 mm.

[0041] In this invention, the pressure of the cold pressing is preferably 8 to 12 MPa, more preferably 10 MPa; the holding time is preferably 1 min.

[0042] In this invention, the sintering temperature is preferably 950–1050°C, more preferably 950°C, 1000°C, or 1050°C, and the holding time is preferably 1–2 hours, more preferably 1 hour. In this invention, the heating rate to the sintering temperature is preferably 3–5°C / min, more preferably 5°C / min.

[0043] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0044] Example 1

[0045] 1 kg of electrolytic manganese slag was immersed in 3 L of 1.5 mol / L sulfuric acid and extracted at 70 °C for 3 h to obtain an extract.

[0046] The obtained extract was mixed with 0.3 kg of calcium carbonate to form ferric hydroxide, and filtered to obtain the first filtrate and the first filter residue.

[0047] Add 0.1 kg of manganese fluoride to the first filtrate to form magnesium fluoride and calcium fluoride, and obtain the second filtrate and the second filter residue;

[0048] Add 0.05 kg of phosphoric acid extractant P204 to the second filtrate to extract manganese, then filter to obtain the third filtrate and the third filter residue. Use 0.05 kg of phosphoric acid extractant P507 to extract cobalt and nickel from the third filtrate to obtain a cobalt-nickel extract and the fourth filter residue.

[0049] The first to fourth filter residues were combined to obtain 0.86 kg of secondary waste residue;

[0050] The secondary waste residue was washed sequentially with water and 0.1 mol / L sodium hydroxide solution, then dried in an oven. After thorough drying, it was mixed evenly with 0.172 kg of waste biomass residue and then ball-milled for 20 hours until the particle size was 0.2 mm.

[0051] 0.03 kg of the ball-milled mixed powder was taken out and cold-pressed at a pressure of 10 MPa for 1 min. The pressed green body was then placed in a tube furnace for sintering in an argon atmosphere. The temperature was increased to 950°C at a rate of 5°C / min and held for 1 h. After sintering, an electromagnetic wave absorbing material was obtained, denoted as EMRs / C-1.

[0052] Figure 1 The above are SEM images of EMRs / C-1 prepared in Example 1. Figure 1 It can be seen that the EMRs / C-1 composite material was successfully prepared, with uniform particle size but few pores, and no porous structure was formed.

[0053] Example 2

[0054] 1 kg of electrolytic manganese slag was immersed in 3 L of sulfuric acid with a mass concentration of 1.2 mol / L and extracted at 70 °C for 3 h to obtain an extract.

[0055] The obtained extract was mixed with 0.3 kg of calcium carbonate to form ferric hydroxide, and filtered to obtain the first filtrate and the first filter residue.

[0056] Add 0.1 kg of manganese fluoride to the first filtrate to form magnesium fluoride and calcium fluoride, and obtain the second filtrate and the second filter residue;

[0057] Add 0.05 kg of phosphoric acid extractant P204 to the second filtrate to extract manganese, then filter to obtain the third filtrate and the third filter residue. Use 0.05 kg of phosphoric acid extractant P507 to extract cobalt and nickel from the third filtrate to obtain a cobalt-nickel extract and the fourth filter residue.

[0058] The first to fourth filter residues were combined to obtain 0.9 kg of secondary waste residue;

[0059] The secondary waste residue was washed sequentially with water and 0.1 mol / L sodium hydroxide solution, then dried in an oven. After thorough drying, it was mixed evenly with 0.135 kg of waste biomass residue and then ball-milled for 20 hours until the particle size was 0.17 mm.

[0060] 0.03 kg of the ball-milled mixed powder was taken out and cold-pressed at a pressure of 10 MPa for 1 min. The pressed green body was then placed in a tube furnace for sintering in an argon atmosphere. The temperature was increased to 1000℃ at a rate of 5℃ / min and held for 1 h. After sintering, an electromagnetic wave absorbing material was obtained, denoted as EMRs / C-2.

[0061] Figure 2 The image shows the SEM image of EMRs / C-2 prepared in Example 2. Figure 2 It can be seen that the EMRs / C-2 composite material was successfully prepared, with uniform particle size and a porous structure.

[0062] Figure 3 The electromagnetic wave absorption performance diagram of EMRs / C-2 prepared in Example 2 is shown below. Figure 3 It can be seen that the material achieves effective absorption of electromagnetic waves at a thickness of about 3 mm, and has a certain electromagnetic wave absorption performance.

[0063] Example 3

[0064] 1 kg of electrolytic manganese slag was immersed in 5 L of sulfuric acid with a mass concentration of 1.5 mol / L and extracted at 70 °C for 3 h to obtain an extract.

[0065] The obtained extract was mixed with 0.3 kg of calcium carbonate to form ferric hydroxide, and filtered to obtain the first filtrate and the first filter residue.

[0066] Add 0.1 kg of manganese fluoride to the first filtrate to form magnesium fluoride and calcium fluoride, and obtain the second filtrate and the second filter residue;

[0067] Add 0.05 kg of phosphoric acid extractant P204 to the second filtrate to extract manganese, then filter to obtain the third filtrate and the third filter residue. Use 0.05 kg of phosphoric acid extractant P507 to extract cobalt and nickel from the third filtrate to obtain a cobalt-nickel extract and the fourth filter residue.

[0068] The first to fourth filter residues were combined to obtain 0.9 kg of secondary waste residue;

[0069] The secondary waste residue was washed sequentially with water and 0.1 mol / L sodium hydroxide solution, then dried in an oven. After thorough drying, it was mixed evenly with 0.176 kg of waste biomass residue and then ball-milled for 20 hours until the particle size was 0.2 mm.

[0070] 0.03 kg of the ball-milled mixed powder was taken out and cold-pressed at a pressure of 10 MPa for 1 min. The pressed green body was then placed in a tube furnace for sintering in an argon atmosphere. The temperature was increased to 1050 °C at a rate of 3 °C / min and held for 1 h. After sintering, an electromagnetic wave absorbing material was obtained, denoted as EMRs / C-3.

[0071] Figure 4 The image shows the SEM image of EMRs / C-3 prepared in Example 3. Figure 3 It can be seen that the EMRs / C-3 composite material was successfully prepared, with uniform particle size but small pores.

[0072] The electromagnetic wave absorption materials prepared in Examples 1-3 were tested using the waveguide method. The test data are shown in Table 1.

[0073] Table 1 Electromagnetic wave absorption test data

[0074] EMRs / C-1 -4.1 EMRs / C-2 -27.3 EMRs / C-3 -5.3

[0075] As can be seen from Table 1, Examples 1 and 3 did not achieve effective absorption of electromagnetic waves; Example 2 has the best reflection loss of -27.4, and its electromagnetic wave absorption performance is better than that of Examples 1 and 3.

[0076] The density of the electromagnetic wave absorbing materials prepared in Examples 1-3 was tested, and the test data were 2.037 g / cm³. 3 2.004 g / cm 3 and 2.044 g / cm 3 It meets the requirements for lightweight electromagnetic wave absorbing materials.

[0077] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for the resource utilization of electrolytic manganese slag, characterized in that, Includes the following steps: 1 kg of electrolytic manganese slag was immersed in 3 L of sulfuric acid with a mass concentration of 1.2 mol / L and extracted at 70 °C for 3 h to obtain an extract. The obtained extract was mixed with 0.3 kg of calcium carbonate to form ferric hydroxide, and filtered to obtain the first filtrate and the first filter residue. Add 0.1 kg of manganese fluoride to the first filtrate to form magnesium fluoride and calcium fluoride, and obtain the second filtrate and the second filter residue; Add 0.05 kg of phosphoric acid extractant P204 to the second filtrate to extract manganese, then filter to obtain a third filtrate and a third filter residue. Use 0.05 kg of phosphoric acid extractant P507 to extract cobalt and nickel from the third filtrate to obtain a cobalt-nickel extract and a fourth filter residue. Combine the first to fourth filter residues to obtain 0.9 kg of secondary waste residue. The secondary waste residue was washed sequentially with water and 0.1 mol / L sodium hydroxide solution, then dried in an oven. After thorough drying, it was mixed evenly with 0.135 kg of waste biomass residue and then ball-milled for 20 hours until the particle size was 0.17 mm. Take out 0.03 kg of ball-milled mixed powder and cold press it at a pressure of 10 MPa for 1 min. Place the pressed green body into a tube furnace for sintering in an argon atmosphere. Heat the furnace at a rate of 5 °C / min to a sintering temperature of 1000 °C and hold for 1 h. After sintering, electromagnetic wave absorbing material is obtained. The reflection loss of the electromagnetic wave absorbing material is -27.3dB.

Citation Information

Patent Citations

  • Preparation method for electrolytic manganese residue porous ceramics

    CN102584316A

  • Method for extracting cobalt and nickel from manganese, cobalt and nickel waste residue

    CN103773961A